In Vivo Confocal Microscopy and Anterior Segment Optical Coherence Tomography Analysis of the Microcystic Keratitis - Michał Dembski; Anna Nowińska; Klaudia Ulfik; Sławomir Teper; Edward Wylęgała (Journal of Ophthalmology)
Purpose. To describe the findings of in vivo confocal microscopy (IVCM) and anterior segment optical coherence tomography (AS-OCT) in a case of bilateral acute microcystic epitheliopathy after daily soft contact lens wear. Methods. IVCM and AS-OCT were used in the course of the bilateral epitheliopathy of a 23-year-old patient at the acute stage of the disease and at recovery after four days of treatment. The images were analyzed and compared. Results. On AS-OCT of the right eye, general hyperreflectivity and the increased thickness of the central corneal epithelium to 150 μm with numerous hyporeflective small, oval cysts were revealed and resolved completely at day 4 after diagnosis and treatment. AS-OCT scans of the left eye revealed oval shaped, hyperreflective material within the corneal epithelium. IVCM of both eyes showed numerous microcysts of different sizes filled with hyperreflective material mostly within superficial epithelial layers. Epithelial cells showed a polymorphism along with disruption of a cytoarchitecture. Basal epithelial cells and anterior stroma showed inflammatory changes. Posterior corneal stroma and endothelium presented normal morphology. Conclusions. Microcystic keratitis appeared as localized microcystic inflammation of epithelium on AS-OCT, which was confirmed by IVCM. Both IVCM and AS-OCT are helpful diagnostic instruments in case of cystic inflammation of corneal epithelium.